Depth Design for Rectangular Stilling Well with Oblique Water Intake - XIE Hongying; QIU Yong; ZHOU Xinyu; GE Yafei; CUN Shoujian (Renmin Zhujiang)
When the topography conditions cannot satisfy the needs of the length of the stilling pool during traditional bottom-flow energy dissipation,the energy can be dissipated by increasing the depth and width of the pool.To obtain suitable depths for a rectangular stilling well under different inflow conditions,we study the influence of well depth on the impact pressure borne by the bottom plate of the stilling well and the relationship between the Froude number of the incident submerged jet and well depth through hydraulic model tests.The research findings are as follows:The impact pressure and the variance of the fluctuating pressure in the impact zone both decrease as well depth increases,although their decreasing amplitudes gradually reduce; the suitable well depth the stilling well needs increases with the Froude number of the incident water flow.Relying on the test results,we also present a fitting formula for the water depth before the hydraulic jump of the incident water flow at the transect at the end of the discharge chute and the suitable depth for the stilling well.The proposed formula is expected to provide a reference for engineering design.